CO‐registration of proton magnetic resonance spectroscopy (1H‐MRS) and diffusion imaging (DMRI) in healthy aging: A prospective study of cerebral neurochemistry and microstructure: Neuroimaging / Normal brain aging. (7th December 2020) - Hone‐Blanchet, Antoine; Shahid, Salman Syed; Krishnamurthy, Lisa; Lin, Qixiang; Levey, Allan I; Lah, James J; Qiu, Deqiang; Crosson, Bruce
Abstract: Background: Changes in brain microstructure are markers of aging and implicate changes at the neurochemical level. Prior magnetic resonance spectroscopy (MRS) works have demonstrated effect of aging on gamma‐aminobutyric acid (GABA) and myo‐inositol (mI), suggesting changes in cellular metabolism and neuroinflammation. Diffusion MRI (dMRI) works have shown that neurite density (NDI) is decreased in aging, suggesting a decrease in dendritic and axonal health. We obtained MRS and dMRI indices co‐registered within the same voxel in the medial frontal cortex (MFC) to investigate how tissue microstructure locally influences neurochemistry. We hypothesized that NDI would predict age‐related changes in concentration of GABA and age‐related neuroinflammation with concentration of mI. Method: Participants: 138 healthy older adults (age 64.8±6.52 years; range 51‐86 years). Informed consent was obtained from all subjects. MRS: acquired on a 3T MRI system with a 32‐channel head coil. PRESS and MEGAPRESS spectra were acquired from a 3x3x3cm voxel positioned in the MFC. GABA and mI levels were estimated with Gannet and LC Model. Segmentation of images was performed with SPM 12. A voxel mask registered to T1 was generated to perform registration of dMRI in the same volume. dMRI: acquired in the axial plane with a multi‐band signal‐shot spin echo echo‐planar sequence (MB acceleration factor = 3). A multi‐shell scheme was used with 3 b0, 10 b150, 10 b350, 64 b1000, 64 b2000, 64 b3000 and 104 b5000 directions. Raw images were processed to reduce signal noise. Analyses: Linear regression analyses were performed: Effect of age with NDI and MRS metabolites as dependent variables. Effect of NDI with MRS metabolites as dependent variables with age as covariate. Result: Age predicted levels of GABA ( B =0.413, P <0.001), mI ( B =0.309, P =0.002), and NDI ( B =‐0.351, P <0.001). NDI predicted levels of GABA ( B =0.24, P =0.005) and mI ( B =‐0.236, P =0.022). Conclusion: This study demonstrates that local microstructure differentially impacts GABA and mI in a healthy aging cohort. It also supports age as a predictor of microstructure and neurochemistry in the MFC. These suggest that neurite density impacts neurochemistry prior to age‐related, clinically significant structural changes and demonstrate relevance of co‐registration of MRS and dMRI in aging.